PENGARUH LINGKUNGAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR SANTRI MDT AT-TAQWA KP. RANCA AYU DESA MAROKO KABUPATEN GARUT - Dewi, Sri Utami (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
Relatioanships with peers have a number of important roles in the development of personal and social development. The most important functions of peers is to provide resources and comparison about the world outside the family. Children receive feedback on their capabilities of its peer group. The interaction among student both in the classroom formed an association which may be one source of extrinsic motivation, namely peers. Togethemess within long time at school can provide its own motivation in the learning process. The purpose of this study is to: (1) explain the level of peer interaction of fifth grade stundents of MDT At-taqwa kp. Ranca Ayu desa Maroko Kab. Garut, (2) explain the motivation level of the fifth students at state MDT Attaqwa kp. Ranca Ayu desa Maroko Kab. Garut, (3) determine the between peer interaction with students motivation in fifth grade state MDT At-taqwa kp. Ranca Ayu desa Maroko Kab. Garut. The results showed that the higher level of peer interaction of the students, the higher students motivation.